Green synthesis of gold nanoparticles (AuNPs) using pathogenic bacteria Acinentobacter baumanii with evulation their antibacterial activity - Khalaf Abbood, Hawraa; Rahim Hateet, Rashid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The current study concentrated on the environmentally friendly production of gold nanoparticles (AuNPs) by pathogenic bacteria, specifically Acinetobacter baumannii, that were isolated from blood. By monitoring the color change of the reaction mixture Tetrachloroauric acid (HAuCl4.3H2O + bacterial filtrate), the production of AuNPs was verified following isolation and molecular identification. Physicochemical tests were used to evaluate the produced AuNPs. The results showed that the particles had a UV spectroscopic peak at a wavelength of 560 nm and that their spherical size ranged from 91 to 43 nm when viewed under a scanning electron microscope Fe-SEM.The chemical components in the bacterial extract have a fundamental impact on the formation of AuNPs as a bioreducing agent, according to the infrared spectrum obtained using the FTIR technique. According to the XRD analysis, the NPs exhibit a cubic crystalline structure, and the EDX-Mapping analysis verified the presence of gold. Furthermore, the antibacterial efficacy of AuNPs against two strains of Gram-positive Staphylococcus aureus and Gram-negative Echerichia coli pathogenic bacteria was confirmed using inhibitory diameters (24 mm and 22 mm) based on the antibiotic gentamicin. with diameter (20mm) as a control at a concentration of 1000 mg/mol as the results showed that the particles have good antibacterial activity